Makna Leksikal dan Gramatikal dalam Lagu Zona Nyaman Fourtwnty (Kajian Semantik) - Rasilva Lulu Zahwania; Hindun Hindun (Jurnal Syntax Admiration, 2024)
This research was conducted to examine the lexical and grammatical meanings of the song Zona Comfort sung by Fourtwnty using sematic studies. Lexical and grammatical meanings themselves are part of sematic studies which are generally found in writing, including song lyrics. Lexical and grammatical meanings themselves are common meanings contained in a language used in communication, both communicating directly and communicating in writing, for example conveying lexical and grammatical meanings contained in song lyrics. This study adopts the song Zona Comfort performed by Fourtwnty because it is felt to contain both lexical and grammatical meanings in it. This research was conducted using a microstructural approach in the form of lexical cohesion and grammatical cohesion. This research is presented in a qualitative descriptive form. Qualitative descriptive data obtained in the form of words, language, meaning, and the results of sentence analysis in the form of lexical and grammatical cohesion. The source of the data obtained from this study is the source of the lyrics of the song Zona Comfort which is analyzed and studies regarding the understanding of lexical and grammatical meanings. The results of this study are that the song Zona Depan performed by the band Fourtwnty contains lexical and grammatical meanings precisely in the aspects of reference, ellipsis and conjunctions in the grammatical meaning. As well as aspects of repetition, anonym, collocation, and synonyms in the lexical meaning.